2007
DOI: 10.1523/jneurosci.2661-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Motor Neuron Disease-Associated Mutant Vesicle-Associated Membrane Protein-Associated Protein (VAP) B Recruits Wild-Type VAPs into Endoplasmic Reticulum-Derived Tubular Aggregates

Abstract: The vesicle-associated membrane protein-associated proteins (VAPs) VAPA and VAPB interact with lipid-binding proteins carrying a short motif containing two phenylalanines in an acidic tract (FFAT motif) and targets them to the cytosolic surface of the endoplasmic reticulum (ER). A genetic mutation (P56S) in the conserved major sperm protein homology domain of VAPB has been linked to motorneuron degeneration in affected amyotrophic lateral sclerosis (ALS) patients. We report that in the CNS, VAPB is abundant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
316
8
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(355 citation statements)
references
References 59 publications
30
316
8
1
Order By: Relevance
“…1A-C). The vacuole-like structures probably correspond to the dilated membranes viewed under light microscopy in cells expressing mutant VAPB (Kanekura et al, 2006;Teuling et al, 2007;Prosser et al, 2008). Interestingly, ,75% of these cells also showed a prominent nuclear envelope defect characterized by separation of the INM and ONM at discrete regions (Fig.…”
Section: Vapb-p56s Causes Swelling Of the Nuclear Envelopementioning
confidence: 91%
See 2 more Smart Citations
“…1A-C). The vacuole-like structures probably correspond to the dilated membranes viewed under light microscopy in cells expressing mutant VAPB (Kanekura et al, 2006;Teuling et al, 2007;Prosser et al, 2008). Interestingly, ,75% of these cells also showed a prominent nuclear envelope defect characterized by separation of the INM and ONM at discrete regions (Fig.…”
Section: Vapb-p56s Causes Swelling Of the Nuclear Envelopementioning
confidence: 91%
“…Convoluted ER tubules have been observed in HeLa cells overexpressing mutant VAPB (Teuling et al, 2007;Fasana et al, 2010), and these were also evident in some cells. However, the most prominent features in cells overexpressing mutant VAPB alone or together with AAAT were large cytoplasmic vacuole-like structures and a dilated or 'herniated' nuclear envelope (Fig.…”
Section: Vapb-p56s Causes Swelling Of the Nuclear Envelopementioning
confidence: 95%
See 1 more Smart Citation
“…Afterward, an ALS (47) model developed in our laboratory by Mitne-Neto et al (48), based on ALS8 patients' cells, has demonstrated that there is a reduction on the VAPB protein levels along motor neuron differentiation from iPSCs. These results complement other studies that show VAPB reduced levels in SALS patients and in SOD1 mice (49,50). These and other findings (51,52) strengthen the evidences that iPSC-derived motor neurons can recapitulate the disease phenotype.…”
Section: Induced Pluripotent Stem Cellssupporting
confidence: 90%
“…However, transgenic mice overexpressing ALS mutant but not wild-type VAPB show TAR DNA-binding protein 43 (TDP-43) positive cytoplasmic inclusions, a pathological hallmark of ALS (Tudor et al, 2010). It has been suggested that mutant VAPB exerts a dominant-negative effect by forming dimeric complexes with wild-type VAPB thereby recruiting it into aggregates (Teuling et al, 2007).…”
Section: Als8 (Vapb)mentioning
confidence: 99%